ZBIEG EGZEKUCJI SĄDOWEJ I ADMINISTRACYJNEJ - Miśtal, Kamil (Zeszyty Prawnicze, 2016)
THE CONCURRENCE OF THE EXECUTION OF COURT ORDERS FOR THE SEIZURE OF PROPERTY ISSUED BY THE POLISH CIVIL AND ADMINISTRATIVE COURTS Summary This study begins with a discussion of the concept of the execution of Polish civil court orders for the seizure of property with an indication of the relevant provisions. A description is given of the assets subject to seizure. The analogous administrative proceedings are presented in a similar way. The author goes on to analyse the provisions in the event of a concurrence of a civil court order with an administrative court order. He considers the implementation of the two orders by a single authority, and discusses the procedural law applicable in the event of concurrence. He continues with a description of the further procedure once the implementing authority has been designated. He also observes that executive proceedings generally take too long. The author uses empirical data from court cases to illustrate his points.